SFI, a sex hormone binding globulin based nomogram for predicting non-alcoholic fatty liver disease in the Chinese population - Hua, Xiaomin; Zhang, Heping; Yang, Wenru; Liu, Guotao; Zhang, Suhua; Wang, Yingcui (Frontiers in Endocrinology, 2023)
Background: The purpose of this study is to establish a novel nomogram model for accurate detection of non-alcoholic fatty liver disease (NAFLD) in the Chinese population based on sex hormone binding globulin (SHBG) and other routine laboratory tests. Methods: A total of 1417 participants (1003 testing and 414 validations) were enrolled into the study. Risk factors independently associated with NAFLD were identified and incorporated in the new nomogram, SFI. The performance of nomogram was assessed by analysis of receiver operating characteristic (ROC) curve, calibration curve, and decision curve. Results: We formulated a new nomogram incorporating four independent factors: SHBG, body mass index (BMI), ALT/AST, and triglycerides (TG). The nomogram achieved good indexes of area under ROC 0.898 (95% confidence interval 0.865–0.926) in predicting NAFLD, which was significantly superior to previously reported models of FLI, HSI, LFS, and LAP. The calibration curve and decision curve demonstrated high performance and clinical utility of the nomogram in predicting NAFLD. Conclusions: The nomogram SFI has high performance in predicting NAFLD in Chinese population and may be used as a cost-effective screening model to assess NAFLD in the general population.